Desulphurization and denitrification of diesel oil using ionic liquids : experiments and quantum chemical predictions - Banerjee, Tamal; Ramalingam, Anantharaj (Amsterdam, Netherlands : Elsevier, 2015)
Desulphurization and Denitrification of Diesel Oil using Ionic Liquids: Experiments and Quantum Chemical Predictions discusses how quantum chemical calculations are applied to investigate the fundamental nature of the IL-sulphur-nitrogen systems at atomic and molecular levels. The book will help readers understand the nature of the structural relationship between molecules such as ionic liquid + aromatic sulphur + aromatic nitrogen system(s). In addition, COSMO-RS (Conductor Like Screening Model for Real Solvents) predictions and subsequent experimentation are discussed to evaluate the performance of ionic liquids for desulphurization and denitrification of diesel oil.
Includes bibliographical references and index.
Vendor-supplied metadata.
Elsevier
Keywords: Diesel fuels -- Desulfurization; Denitrification; Ionic solutions; Quantum chemistry; TECHNOLOGY & ENGINEERING / Engineering (General); Electronic books